Evaluasi Proses Pembelajaran dan Evaluasi Pendidikan: Perspektif Kontemporer dalam Peningkatan Kualitas Pendidikan - Firman; Zulfia, Namira; Muzaki, Ahmad; Syam, Wistiani (LPPM IAIN Sorong, 2026)
Evaluation of the learning process and educational evaluation are strategic elements in an education quality assurance system oriented toward continuous improvement. This article aims to comprehensively examine the concepts, functions, types, and implementation of learning evaluation and educational evaluation in the context of secondary education, with a case study at Madrasah Aliyah Kaimana. This study employs a qualitative approach with a descriptive-analytical design. Data were collected through observation, in-depth interviews, documentation, and questionnaires involving the school principal, teachers, and students. The findings indicate that the school has implemented a relatively comprehensive and integrated evaluation system, encompassing formative, summative, and diagnostic evaluations, as well as competency-based evaluation supported by the use of digital technology. Learning evaluation functions not only as a tool for measuring learning outcomes but also as a means of pedagogical reflection for teachers and as a basis for school managerial decision-making. However, this study also identifies several challenges, including the suboptimal consistency in the implementation of differentiated learning, disparities in digital competencies between senior and junior teachers, limitations in guidance and counseling services, and issues related to the quality and timeliness of learning feedback. The practical implications of this study emphasize the importance of strengthening teacher capacity, systematically utilizing evaluation data, and ensuring the active involvement of all stakeholders in the evaluation process. Theoretically, this study contributes to the development of a holistic, participatory educational evaluation model oriented toward the continuous improvement of educational quality